2018
DOI: 10.2478/pjct-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release urea encapsulated by ethyl cellulose/butyl acrylate/vinyl acetate hybrid latex

Abstract: Fertilizer encapsulation through polymer membranes can reduce fertilizer losses and minimize environmental pollution. In this paper, an emulsion of ethyl cellulose (EC)/vinyl acetate (VAc)/butyl acrylate (BA) was successfully prepared by pre-emulsifi ed semi-continuous seed emulsion polymerization. EC/BA/VAc fi lms showed biodegradability. The infl uence of the EC content on the properties of EC/BA/VAc fi lms was also investigated by DSC, a water absorbency analysis, etc. Controlled-release urea encapsulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Thus, the open space for water determines the rate of water penetration or exchange, which affects the release rate of nutrients. Several studies applied this property to produce SRFs [17,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the open space for water determines the rate of water penetration or exchange, which affects the release rate of nutrients. Several studies applied this property to produce SRFs [17,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…42−44,48−53 Specifically, fertilizer delivery systems based on biobased polymers might result in significant advantages over their fossil fuel-based counterparts: good biocompatibility and affinity for biomolecules present in the agricultural soil, biodegradability, lower costs, high water retention capacity, improvement in soil permeability, and enhanced NUE into the natural soil matrix. 13,49,54 Cost− benefits analysis for biobased polymer CRFs is weighted in the significant increase in crop production. 55−57 For instance, Zhang et al 58 found that the cost of poly(acrylic acid)-coated lignin−clay nanohybrid CRF was reduced 74−75% as compared to urea-formaldehyde fertilizer and increased by only 16−18% compared to bare urea.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, biobased polymers extracted from benign organic wastes are becoming a feasible alternative to produce CRFs as they could be easily degraded by native soil microorganisms. , Specifically, fertilizer delivery systems based on biobased polymers might result in significant advantages over their fossil fuel-based counterparts: good biocompatibility and affinity for biomolecules present in the agricultural soil, biodegradability, lower costs, high water retention capacity, improvement in soil permeability, and enhanced NUE into the natural soil matrix. ,, Cost–benefits analysis for biobased polymer CRFs is weighted in the significant increase in crop production. For instance, Zhang et al found that the cost of poly­(acrylic acid)-coated lignin–clay nanohybrid CRF was reduced 74–75% as compared to urea-formaldehyde fertilizer and increased by only 16–18% compared to bare urea. Likewise, Tang et al reported that the production cost of a CRF coated with sodium alginate is up to five times higher than bare urea, yet only twice as compared to a commercial CRF urea fertilizer coated with a synthetic polymer (i. e., Kingenta ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only a few have reported cellulose-based EEFs in forms other than hydrogels. Solution-casting of emulsions based on ethylcellulose, vinyl acetate, butyl acrylate, and urea has been performed to obtain films for slow nitrogen release, i.e., 84.1% after 42 days in water (Li et al, 2018). Most recently, double-coating urea having ethylcellulose as an inner layer and cellulose-based superabsorbent (pretreated cellulose grafted with acrylic acid and acrylamide) as outer layer slowed nitrogen release in soil to 58.6% within 15 days (Zhang and Yang, 2020).…”
Section: Introductionmentioning
confidence: 99%